Blue Balls of Fire and the Ethics of Spectatorship: Verlaine, Yeats, Beckett - Alexandra Poulain (Angles)
This paper looks at three short dramatic scenes by Paul Verlaine, W. B. Yeats and Samuel Beckett which all pick up that most conventional of theatrical themes, thwarted love, only in a disturbing way, by shifting the focus from the torments of the soul to the painful embodied experience of sexual frustration, and by having it performed not by youthful “star-crossed lovers”, but by ambiguously incarnated revenants, or by decrepit, nearly dead old people. I first suggest that a certain filiation, conscious or not, runs from one of Verlaine’s most famous poems, “Colloque sentimental”, through the dance of the ghosts in Yeats’s “play for dancers” The Dreaming of the Bones, to the “love scene” played out by Nagg and Nell out of their respective dustbins in Beckett’s Endgame. More importantly, I argue that the three pieces ask uncomfortable questions about the ethics of spectatorship and invite us to think critically about the conceptualising of theatre as a “face-to-face encounter with the Other”, a notion inspired by Levinas which has gained currency since the “ethical turn” hit theatre studies in the mid-2000s. This paradigm, I further suggest, is applied inaccurately to the theatrical encounter, especially in such contemporary productions as Milo Rau’s 2019 show Orestes in Mosul, which rather rests on a problematic ethics of empathy, a notion foreign to Levinas. The three scenes by Verlaine, Yeats and Beckett, on the other hand, offer an alternative model of unempathetic spectatorship which, paradoxically, may go further towards allowing the presence of radical Others on the stage.